2011
DOI: 10.1002/adsc.201100219
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Phospha‐Michael Reaction of Diphenyl Phosphonate with Nitroolefins Utilizing Conformationally Flexible Guanidinium/Bisthiourea Organocatalyst: Assembly‐State Tunability in Asymmetric Organocatalysis

Abstract: A catalytic enantioselective phospha-Michael reaction of diphenyl phosphonate to nitroolefins was achieved by utilizing a 1,3-diamine-tethered guanidinium/bisthiourea organocatalyst. The procedure is applicable to nitroolefins having various aromatic and aliphatic substituents, and enables an efficient access to phospha-Michael products with 90-98% ee. Monomeric or oligomeric active species of the catalyst can be utilized, depending on the presence or absence of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…In contrast, efficient 1,3‐ and 1,4‐diamine‐derived organocatalysts [with the exception of (BINAM)‐based catalysts] are very rare. Conformationally flexible guanidine‐bisthiourea organocatalysts have been used in asymmetric 1,4‐type Friedel–Crafts reaction of phenols and phospha‐Michael reaction of diphenyl phosphonate with nitroolefins . Ferrocene‐based, and self‐assembled proline‐1,3‐diamine‐thiourea bifunctional organocatalysts showed high enantioselectivity in Michael additions of acetylacetone and aldehydes to nitroolefins.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, efficient 1,3‐ and 1,4‐diamine‐derived organocatalysts [with the exception of (BINAM)‐based catalysts] are very rare. Conformationally flexible guanidine‐bisthiourea organocatalysts have been used in asymmetric 1,4‐type Friedel–Crafts reaction of phenols and phospha‐Michael reaction of diphenyl phosphonate with nitroolefins . Ferrocene‐based, and self‐assembled proline‐1,3‐diamine‐thiourea bifunctional organocatalysts showed high enantioselectivity in Michael additions of acetylacetone and aldehydes to nitroolefins.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Nagasawa and Sohtome et al attempted the Michael addition of diphenylp hosphonate to nitroolefins with the help of the conformationally flexible guanidine-thiourea catalyst 7 (Scheme 26). [44] Initial screens of different solvents showed no obvious effect on the enantiomeric preference, but the addition of water as ac o-solvent promoted the enantioselectivity to 95 % ee values. Under optimal reactionc onditions, both aromatic and aliphatic nitroolefins led to corresponding products with excellent enantioselectivity (90-98 % ee values).…”
Section: Phospha-michaelr Eactionmentioning
confidence: 98%
“…Nagasawa and Sohtome et al. attempted the Michael addition of diphenyl phosphonate to nitroolefins with the help of the conformationally flexible guanidine‐thiourea catalyst 7 (Scheme ) . Initial screens of different solvents showed no obvious effect on the enantiomeric preference, but the addition of water as a co‐solvent promoted the enantioselectivity to 95 % ee values.…”
Section: Chiral Guanidines As Asymmetric Catalystsmentioning
confidence: 99%
“…A substantial amount of research has shown good conversion and enantioselectivities of β‐nitro phosphonate in asymmetric Michael addition of diphenylphosphite to nitroalkenes using bi‐functional organocatalyst . However, high solubility of the catalyst in the reaction medium adversely affects the separation and recyclability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%